Superior bending and impact properties of SiC matrix composites infiltrated with an aluminium alloy. Issue 5 (1st April 2017) - Wang, Wei; Li, Qiang; Ma, Ruina; Cao, Xiaoming; Cui, Yaqi; Fan, Yongzhe; Yang, Tai; Liu, Baoxi
Abstract: A simple process based on melt infiltration was used to modify a silicon carbide (SiC) ceramic and thus improve its mechanical properties. SiC ceramics infiltrated with an Al alloy for 2 h, 4 h, 6 h, and 8 h exhibited outstanding mechanical performance. The three-point bending strength, four-point bending strength, and impact toughness of the SiC ceramics increased by 125–135%, 170–180%, and 140%, respectively, after infiltration with the Al alloy at 900 °C for 4–6 h. The maximum three-point bending strength, four-point bending strength, and impact toughness achieved were 430 MPa, 360 MPa, and 3.5 kJ/m 2, respectively. Analysis of the processing conditions and microstructure demonstrated that the molten Al alloy effectively infiltrated the gaps between the SiC particles, forming a compact structure with the particles, and some of the Al phases reacted with Si to form Al-Si eutectic phases. Moreover, the results showed that a reaction layer is present on the surface of the SiC sample, which mainly contains the Ti3 SiC2 phase. Both complete infiltration with the Al alloy and the formation of the Ti3 SiC2 phase contributed to the improvement of the mechanical properties.